The Economic Case for Open Source Foundations. - Riehle, Dirk (Computer (00189162), 2010)
The article discusses open source foundation which is a group of people or companies helping one another to develop community open source software. Apache Software Foundation and Eclipse Foundation are two examples. One primary reason for joining a foundation is to save costs for software development and also to increase revenue through sales of complementary products. Foundations also act as steward of the software being made and ensures its perpetuity. Furthermore, they also take care of intellectual property rights issues related to the software.